In situ biospectroscopic investigation of rapid ischemic and postmortem induced biochemical alterations in the rat brain - Hackett, Mark; Britz, C.; Paterson, P.; Nichol, H.; Pickering, I.; George, G. (American Chemical Society, 2015)
© 2014 American Chemical Society. Rapid advances in imaging technologies have pushed novel spectroscopic modalities such as Fourier transform infrared spectroscopy (FTIR) and X-ray absorption spectroscopy (XAS) at the sulfur K-edge to the forefront of direct in situ investigation of brain biochemistry. However, few studies have examined the extent to which sample preparation artifacts confound results. Previous investigations using traditional analyses, such as tissue dissection, homogenization, and biochemical assay, conducted extensive research to identify biochemical alterations that occur ex vivo during sample preparation. In particular, altered metabolism and oxidative stress may be caused by animal death. These processes were a concern for studies using biochemical assays, and protocols were developed to minimize their occurrence. In this investigation, a similar approach was taken to identify the biochemical alterations that are detectable by two in situ spectroscopic methods (FTIR, XAS) that occur as a consequence of ischemic conditions created during humane animal killing. FTIR and XAS are well suited to study markers of altered metabolism such as lactate and creatine (FTIR) and markers of oxidative stress such as aggregated proteins (FTIR) and altered thiol redox (XAS). The results are in accordance with previous investigations using biochemical assays and demonstrate that the time between animal death and tissue dissection results in ischemic conditions that alter brain metabolism and initiate oxidative stress. Therefore, future in situ biospectroscopic investigations utilizing FTIR and XAS must take into consideration that brain tissue dissected from a healthy animal does not truly reflect the in vivo condition, but rather reflects a state of mild ischemia. If studies require the levels of metabolites (lactate, creatine) and markers of oxidative stress (thiol redox) to be preserved as close as possible to the in vivo condition, then rapid freezing of brain tissue via decapitation into liquid nitrogen, followed by chiseling the brain out at dry ice temperatures is required.